Perception of local youth in Sabah towards career in oil palm plantation - Mohamad Amizi Ayob; Norehan Abdullah; Jamal Ali; Roslina Kamaruddin (Asia Pacific Institute of Advanced Research (APIAR), 2015)
Sabah is the biggest state in contributing to the oil palm commodity in Malaysia. At present,the total hectares are 1.51 million hectares (MPOB 2015) and 28% of palm oil came from this state. With the rapid expansion of oil palm plantation and required high labour intensive in this sector, more than 80 % of plantation labor in this state mainly came from Indonesia and Philippines. The pressing issue now is the rising social issues of the illegal foreign workers without work permit thus; the best answer is to hire local youth. Nevertheless, the problem is compounded by the fact that it is difficult to hire the local youth workers and the progress on mechanization has also not been encouraging. Therefore, this study which was conducted in the State of Sabah attempts to identify the perceptions and factors that can attract more local youth to work in oil palm plantation. A survey method through questionnaire was used to collect data from 156 of local youth between 16 years to 40 years of age as focused respondents which were selected using random sampling method. Descriptive statistics was applied in order to rank the factors according to the demographic factors of the respondents such as gender, age, marital status, education level, parents background, location and working status that affecting the factors of perceptions of local youth to work in oil palm plantation in Sabah.